Implementing an In-House Digital Acknowledgment Solution for SAP MRA Returns in the Pharmaceutical Industry - Mohammed Abid Momin (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This article comprehensively implements an in-house digital acknowledgment solution for pharmaceutical returns management using the SAP MRA (Material Returns Authorization) system. The solution addresses critical challenges in the pharmaceutical industry’s return process, including regulatory compliance, operational efficiency, and cost optimization. Integrating SAP S/4 HANA, SAP PI/PO, and Microsoft Outlook provides a robust framework for handling return requests through multiple channels while maintaining stringent security standards. The implementation demonstrates significant improvements in processing times, customer satisfaction, and cost reduction through automation and digital transformation. The solution’s architecture emphasizes scalability, security, and performance optimization, incorporating advanced features such as digital signatures, real-time monitoring, and automated workflow management. This article details the technical configuration, system architecture, end-to-end process implementation, and security framework while highlighting the business impact and future enhancement opportunities aligned with Industry 4.0 principles.